Finding Strength in Challenges: a Literature Review on the Role of Growth Mindset and Academic Stress in University Students - Wulan Rahmalia Permatasari; Ratna Dyah Suryaratri; Lussy Dwiutami Wahyuni; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Students are constantly faced with various challenges and academic pressures that have the potential to cause academic stress. On the other hand, a growth mindset is based on the belief that abilities can be developed through effort, effective strategies, and perseverance. A growth mindset tends to perceive challenges as opportunities or strengths for personal growth and development. A growth mindset is considered a protective factor in facing academic challenges and pressures. This study aims to analyse the dynamics the role of growth mindset and academic stress among students. The method used is a literature review by examining relevant scientific articles related growth mindset and academic stress. The articles were retrieved from databases such as Google Scholar, Scopus, EBSCO, and Publish & Perish. From 1.550 articles that only 20 publications were relevant articles published were identified in the last six years from 2019 to 2025. The review found a negative relationship between growth mindset and academic stress, where students with a high growth mindset tend to experience lower levels of academic stress. Growth mindset serves as a protective factor, helping university students interpret academic pressure as a challenge that can be overcome, use adaptive coping strategies, persist more in completing academic tasks, and enhance their resilience and academic motivation. In addition, the relationship between growth mindset and academic stress is dynamic and influenced by mediator and moderator variables, such as emotion, student engagement, as well as psychological and psychological factors. Growth mindset interventions have been proven effective in reducing academic stress while supporting students’ well-being. These findings emphasize the importance of developing a growth mindset as a preventive strategy and intervention in the context of higher education to help students cope with increasingly complex academic demands.